1971
DOI: 10.2118/3044-pa
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of Micellar Solutions To Improve Water Injectivity

Abstract: By removing residual oil and organic skins from the vicinity of a well, water injection rates can be increased. The micellar compositions described here are highly effective for this purpose and are applicable under widely divergent field mixing and reservoir conditions. Introduction To achieve favorable oil productivity during a waterflood project, water injection rates must be maintained at a high level. Acidizing and fracturing are established techniques f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

1977
1977
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…Moreover, it is interesting to note that these formulations, when equilibrated with oil, produce middle phase microemulsion with very low interfacial tension (< 10" 3 dynes/cm). Similar results were also obtained using ethoxylated alcohols in surfactant formulations by previous investigators (47). It is interesting that the ethoxylated sulfonate alone (curve F in Figure 10) is unable to produce ultralow interfacial tension.…”
Section: Phase Behaviorsupporting
confidence: 86%
“…Moreover, it is interesting to note that these formulations, when equilibrated with oil, produce middle phase microemulsion with very low interfacial tension (< 10" 3 dynes/cm). Similar results were also obtained using ethoxylated alcohols in surfactant formulations by previous investigators (47). It is interesting that the ethoxylated sulfonate alone (curve F in Figure 10) is unable to produce ultralow interfacial tension.…”
Section: Phase Behaviorsupporting
confidence: 86%
“…where IS] is the concentration of added electrolyte, and /3 is the fractional counterion binding on the micelles. Note that counterion comes from both added salt and the anionic surfactant upon dissolution (left hand side of Equation [4]); the counterion from these two contributions is assumed to be of the same type. The right hand side of Equation [4] accounts for the total counterion in solution as either unassociated species, or bound on micelles.…”
Section: Theorymentioning
confidence: 99%
“…Note that counterion comes from both added salt and the anionic surfactant upon dissolution (left hand side of Equation [4]); the counterion from these two contributions is assumed to be of the same type. The right hand side of Equation [4] accounts for the total counterion in solution as either unassociated species, or bound on micelles. The fractional counterion binding is defined as the ratio of the number of counterions bound on the mixed micelle to the number of anionic surfactant molecules in that mixed micelle.…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Dauben and Froning (14) have shown that, depending upon salt concentration, phase separation can occur at 150°F with a solution that is stable at room temperature. Dauben and Froning (14) have shown that, depending upon salt concentration, phase separation can occur at 150°F with a solution that is stable at room temperature.…”
Section: E Temperaturementioning
confidence: 99%